Analisis Manajemen Operasional Sumber Daya & Proses Produksi: Studi Kasus Pada PT. Indofood Sukses Makmur Tbk - Amar Zulfan Al-Rabbani; Julfi Fikri Maulana; M. Bima Herlambang (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
PT Indofood Sukses Makmur Tbk is a company engaged in the production of various types of food and beverages. In an effort to improve the efficiency and effectiveness of its operational activities, PT Indofood has implemented various operational strategies. This analysis discusses the implementation of PT Indofood Sukses Makmur Tbk's operational strategies including the use of the Just In Time system, ABC analysis, vendor-managed inventory, and inventory management software. The results show that PT Indofood's operational strategies are effective in improving the efficiency and effectiveness of its operational activities. In this way, the company can reduce the risk of stock-outs or excess inventory and improve the quality of its products.